Tools and Techniques for Real-time Data Acquisition and Analysis in Brain Computer Interface studies using qEEG and Eye Tracking in Virtual Reality Environment. Issue 3 (2015) - Boukhalfi, Tarik; Joyal, Christian; Bouchard, Stéphane; Neveu, Sarah Michelle; Renaud, Patrice
Abstract: In this paper, we present the pipeline of data acquisition and analysis used in the ARViPL lab at the Montreal Philippe-Pinel Institute for different studies related to forensic psychiatry in Virtual Reality (VR) environment and we discuss the different challenges that we encounter during the experiments when combining different new technologies that help researchers to better understand the underlying mechanisms of various mental health disorders.